Catering To Guest Satisfaction: Assessing The Influence Of Service Quality And Sharia Compliance - Tuwuh Adhistyo Wijoyo; Julian Andriani Putri; Fiolita Aurel Aninditya; Umar Abdul Jabbar (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This research aims to examine the influence of service quality and the implementation of Sharia principles on guest satisfaction at Hotel Namira Syariah in Pekalongan. The population of this study consists of guests who have stayed at Hotel Namira Syariah Pekalongan, with a sample size of 96 respondents. Data collection was done through questionnaires, and the analysis includes validity, reliability, multiple linear regression analysis, t-test, F-test, and coefficient of determination analysis. The results of this study indicate that service quality has a positive impact on guest satisfaction, and the implementation of Sharia principles also has a positive influence on guest satisfaction. The F-test shows that service quality and the implementation of Sharia principles have a simultaneous and significant impact on guest satisfaction at Hotel Namira Syariah Pekalongan. In the multiple linear regression analysis, the variable of service quality has a more dominant influence on guest satisfaction (the dependent variable) with a coefficient of 0.351. The findings of this study suggest that to enhance guest satisfaction at Hotel Namira Syariah Pekalongan, there is a need for improvements in both service quality and the implementation of Sharia principles.